The Effectiveness of a Multicenter Quality Improvement Collaborative in Reducing Inpatient Mortality. Issue 2 (June 2015) - Kroch, Eugene; Duan, Michael; Martin, John; Bankowitz, Richard; Kugel, Marla
<x xml:space="preserve">Abstract</x> Motivation and Background This study examines the evidence that a particular quality improvement collaborative that focused on Quality, Efficiency, Safety and Transparency (QUEST) was able to improve hospital performance. Setting The collaborative included a range of improvement vehicles, such as sharing customized comparative reports, conducting online best practices forums, using 90-day rapid-cycle initiatives to test specific interventions, and conducting face-to-face meetings and quarterly one-on-one coaching sessions to elucidate opportunities. Methods With these kinds of activities in mind, the objective was to test for the presence of an overall "QUEST effect" via statistical analysis of mortality results that spanned 6 years (2006-2011) for more than 600 acute care hospitals from the Premier alliance. Results The existence of a QUEST effect was confirmed from complementary approaches that include comparison of matched samples (collaborative participants against controls) and multivariate analysis. Conclusion The study concludes with a discussion of those methods that were plausible reasons for the successes.